Literacy and the second language learner - Sullivan, JoAnn Hammadou (Emerald Publishing Limited : Information Age, 2002)
The field of second language learning research has grown rapidly in recent years. Educators have become increasingly aware that pedagogical knowledge varies significantly from one subject domain to the next and that findings from educational research in one domain are not necessarily applicable to the next. Researchers in second language learning are adding to our understandings of secondlanguage specific pedagogy. There exists a need, therefore, for an outlet for these ever improving understandings of this content-specific pedagogy. The new book series, Research in Second Language Learning, will provide just such an outlet. The series invites articles from all methodological approaches to research. The series will promote a research-based approach to the decision-making process in second language teaching/learning.
Keywords: Language and languages -- Study and teaching.; Literacy.; Education -- Philosophy, Theory & Social Aspects.; Philosophy and theory of education.; elektronické knihy; electronic books